2020
DOI: 10.7554/elife.56551
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of sonic hedgehog signaling causes hearing loss in ciliopathy mouse models

Abstract: Defective primary cilia cause a range of diseases known as ciliopathies, including hearing loss. The etiology of hearing loss in ciliopathies, however, remains unclear. We analyzed cochleae from three ciliopathy mouse models exhibiting different ciliogenesis defects: Intraflagellar transport 88 (Ift88), Tbc1d32 (a.k.a. bromi), and Cilk1 (a.k.a. Ick) mutants. These mutants showed multiple developmental defects including shortened cochlear duct and abnormal apical patterning of the organ of Corti. Although cilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…Indeed, we found that defective GLI activator/repressor functions (GLI1 and GLI3) could help to explain the abnormal cochlear development in Osbpl2 –/– mice. Our findings were consistent with a previous report that defective GLI activator/repressor functions, short cochlea, and extra rows of HCs were found in the distal region of the cochlea when Shh signaling transduction was impaired ( 12 ). In addition, we found that OSBPL2 was essential to SMO accumulation in cilia after activation of the Shh signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Indeed, we found that defective GLI activator/repressor functions (GLI1 and GLI3) could help to explain the abnormal cochlear development in Osbpl2 –/– mice. Our findings were consistent with a previous report that defective GLI activator/repressor functions, short cochlea, and extra rows of HCs were found in the distal region of the cochlea when Shh signaling transduction was impaired ( 12 ). In addition, we found that OSBPL2 was essential to SMO accumulation in cilia after activation of the Shh signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
“…Auditory hair cells (HCs) are mechanoreceptors of the auditory system and each HC has an apically located hair bundle made up of a single kinocilium and many stereocilia ( 11 ). Hearing loss (HL) in relation to HCs’ ciliary defects is also considered to be a kind of ciliopathy ( 12 ). To date, studies on cilia-related HL have mainly been focused on stereocilia, which are the key organelles responsible for the conversion of mechanical energy into electrical signals ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of the tonotopic features are conserved between the chicken and mouse. For example, the length of the hair bundle, which are composed of tens of stereocilium arranged in a stair-case pattern, is shorter at the base and gradually longer toward the apex, whereas the width of hair bundle is wider at the base and gradually narrower toward the apex ( Son et al, 2015 ; Moon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in some ciliary genes encoding important intraflagellar transport (IFT) proteins such as Ift88 can also cause hearing defects. Ift88 conditional knockout mice exhibit shortened cochlear ducts with multiple extra rows of HCs at the apex, severe hair bundle polarity defects, and premature differentiation of HCs ( Moon et al, 2020 ). Other studies have shown that the phenotypes of these knockout mice all include kinocilium loss, disorderly arrangement of stereocilia of different lengths, short and collapsed structural defects, and mislocation of centrosomes ( Tarchini and Lu, 2019 ).…”
Section: The Kinocilia Of Cochlear Hair Cellsmentioning
confidence: 99%